Analisis Pengambilan Keputusan Taktis: Tetap Mempertahankan Koran Cetak atau Mengganti ke Media Online - Maryati, Ulfi; Putri, Kurniawati; Yentifa, Armel; Maretha Rissi, Dita (Akuntansi dan Manajemen, 2020)
Printed Newspaper readers began to decline with development of technology, and online media readers increased. Printed newspaper companies must take a decision whether to keep the printed newspaper or change to online media. This research is a quantitative applied research using a case study approach. Data collection techniques used were interviews, observation and documentation. This study uses primary data, the analytical method used is thematic analysis, Hansen Mowen's tactical decision making steps, and rational theory models. The results of this research that switching to online media is more profitable going forward for companies, because online media do not cost as much as printed newspapers. Online media does not require ink, paper and operational vehicles such as print newspapers.